Evaluation of the effect of c.2946 + 1G > T mutation on splicing in the SCN1A gene. (February 2015) - Ben Mahmoud, Afif; Ben Mansour, Riadh; Driss, Fatma; Baklouti-Gargouri, Siwar; Siala, Olfa; Mkaouar-Rebai, Emna; Fakhfakh, Faiza
Graphical abstract: Highlights: Mutagenesis PCR was employed to induce a c.2946 + 1G > T mutation The c.2946 + 1G > T mutation caused a total skipping of exon 15. The c.2946 + 1G > T mutation lead to a deletion of the amino acids (853 Leu – 971 Val). The c.2946 + 1G > T mutation was predicted by the human splicing finder (HSF). Abstract: Mutations in the SCN1A gene have commonly been associated with a wide range of mild to severe epileptic syndromes. They generate a wide spectrum of phenotypes ranging from the relatively mild generalized epilepsy with febrile seizures plus (GEFS+) to other severe epileptic encephalopathies, including myoclonic epilepsy in infancy (SMEI), cryptogenic focal epilepsy (CFE), cryptogenic generalized epilepsy (CGE) and a distinctive subgroup termed as severe infantile multifocal epilepsy (SIMFE). The present study was undertaken to investigate the potential effects of a transition in the first nucleotide at the donor splice site of intron 15 of the SCN1A gene leading to CGES. Functional analyses using site-directed mutagenesis by PCR and subsequent ex-vivo splicing assays, revealed that the c.2946 + 1G > T mutation lead to a total skipping of exon 15. The exclusion of this exon did not alter the reading frame but induced the deletion of the amino acids (853 Leu −971 Val) which are a major part in the fourth, fifth and sixth transmembrane segments of the SCN1A protein. The theoretical implications of the splice site mutations predicted with the bioinformatic tool human splice finder were investigated and compared with the results obtained by the cellular assay.